Exister et résister dans les marges urbaines Les villes du Bassin méditerranéen - CATTEDRA, RAFFAELE (Territoires, environnement, sociétés, 2021)
Essential book for those who question the political dimension of the widening social and spatial inequalities. Based on in-depth fieldwork, it delivers a detailed analysis of the mechanisms of marginalization, their effects and the resistance of the inhabitants, in working-class neighborhoods of cities in the Mediterranean Basin.